Analisis Model Kebijakan Kurikulum Merdeka di Indonesia - Mohammad Rafatta Umar; Charren Galuh Indraswari; Dwi Desky Setiawan; Reivania Calista; Fakthuri Fatkhuri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Education is important for the lives of people in a country. In order to create an educational system that is organized and has a vision, a policy in the form of a curriculum is needed. In a country that adheres to a democratic system, it is necessary to involve or participate the community in the policy formulation and implementation process. This policy paper investigates the Merdeka Curriculum policy model created and implemented by the Ministry of Education and Culture. Public policy models include top-down, bottom-up and a combination of the two. The research method used in this article is qualitative with data sources obtained from books, scientific articles, and other credible information found on the internet. In the policy formulation process, studies were conducted and the government involved parents. In addition, in the implementation process, the Merdeka Curriculum is carried out in stages with a trial period carried out by several schools called Mover Schools. In addition, the policy also has an evaluation instrument in the form of a Minimum Competency Assessment. Based on the findings related to this policy, it can be concluded that the policy model in the Merdeka Curriculum is bottom-up.